The effect of leptin replacement on sleep-disordered breathing in the leptin-deficient ob/ob mouse - Pho, H. (J Appl Physiol (1985), 2015)
Obese leptin-deficient (ob/ob) mice demonstrate defects in upper airway structural and neuromuscular control. We hypothesized that these defects predispose to upper airway obstruction during sleep, and improve with leptin administration. High-fidelity polysomnographic recordings were conducted to characterize sleep and breathing patterns in conscious, unrestrained ob/ob mice (23 wk, 67.2 ± 4.1 g, n = 13). In a parallel-arm crossover study, we compared responses to subcutaneous leptin (1 μg/h) vs. vehicle on respiratory parameters during NREM and REM sleep. Upper airway obstruction was defined by the presence of inspiratory airflow limitation (IFL), as characterized by an early inspiratory plateau in airflow at a maximum level (V̇imax) with increasing effort. The severity of upper airway obstruction (V̇imax) was assessed along with minute ventilation (V̇e), tidal volume (V(T)), respiratory rate (RR), inspiratory duty cycle, and mean inspiratory flow at each time point. IFL occurred more frequently in REM sleep (37.6 ± 0.2% vs. 1.1 ± 0.0% in NREM sleep, P < 0.001), and leptin did not alter its frequency. V̇imax (3.7 ± 1.1 vs. 2.7 ± 0.8 ml/s, P < 0.001) and V̇e increased (55.4 ± 22.0 vs. 39.8 ± 16.4 ml/min, P < 0.001) with leptin vs. vehicle administration. The increase in V̇e was due to a significant increase in V(T) (0.20 ± 0.06 vs. 0.16 ± 0.05 ml, P < 0.01) rather than RR. Increases in V̇e were attributable to increases in mean inspiratory flow (2.5 ± 0.8 vs. 1.8 ± 0.6 ml/s, P < 0.001) rather than inspiratory duty cycle. Similar increases in V̇e and its components were observed in non-flow-limited breaths during NREM and REM sleep. These responses suggest that leptin stabilized pharyngeal patency and increased drive to both the upper airway and diaphragm during sleep.